A Survey of Government Regulation and Intervention in Financial Markets - Klapper, Leora; Zaidi, Rida (Washington, DC: World Bank, 2012)
The financial literature documents a positive and robust relationship between development of financial systems and economic growth and a causal relationship between strong financial systems and per capita income. Policy prescriptions for developing countries suggest that governments should not attempt to engineer credit expansion and financial system development but rather limit their involvement to developing a sound business environment.